DISTORTION OF THE WILL OF PEOPLE VOTING OUTSIDE VOTING PREMISES - O. A. Kravchenko (Вестник Кемеровского государственного университета, 2014)
The paper is devoted to the revelation of distortion of the will of people voting outside voting premises. The formallegal method of research is applied. As the result of the study the ways of distorting the will of people voting outside voting premises were identified. It is concluded that the distortion of the will of voters voting outside voting premises is possible when portable ballot boxes comprise the number of ballots, which clearly contradicts the physical capabilities of precinct election commissions. Another conclusion states that public control over the voting outside voting premises can not be fully exercised. The identified ways of distorting people’s will must be eliminated by the electoral legislation ban on voting outside voting premises.